2022
DOI: 10.5205/1981-8963.2022.253285
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade De Vida (Do)no Trabalho De Profissionais Da Atenção Primária Em Saúde: Um Estudo Com O TQWL-42 E De Entrevistas

Abstract: Objetivo: compreender os elementos que compõem a Qualidade de Vida no Trabalho (QVT) na perspectiva dos profissionais da Estratégia de Saúde da Família em um município do Triângulo Mineiro. Métodos: é uma pesquisa quantitativa/qualitativa, realizada com todos os profissionais de uma Unidade Básica de Saúde da Família. Os dados foram obtidos por meio do questionário Total Quality of Work Life-42 e entrevista qualitativa, submetidos à análise descritiva através do software do instrumento e análise temática de co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 16 publications
(8 reference statements)
0
0
0
Order By: Relevance
“…In the aforementioned study, it was suggested that it is more meaningful to focus on improving the work environment than on individual factors. Although personal resilience is a predictor of QoL, work factors such as resource adequacy had a greater impact ( 21 ) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the aforementioned study, it was suggested that it is more meaningful to focus on improving the work environment than on individual factors. Although personal resilience is a predictor of QoL, work factors such as resource adequacy had a greater impact ( 21 ) .…”
Section: Discussionmentioning
confidence: 99%
“…No referido estudo, sugeriu-se que é mais significativo focar em melhora no ambiente de trabalho do que em fatores individuais. Embora a resiliência pessoal seja um preditor de QV, os fatores do trabalho, como adequação de recursos, impactaram mais ( 21 ) .…”
Section: Discussionunclassified
See 2 more Smart Citations